Doppler Echocardiographic Analysis of the Transmitral Flow Velocity Profile in Patients with Ventricular Septal Defects - Stojnic, Bojan (1989)
Using continuous-wave Doppler echocardiography, we evaluated the mitral flow velocity pattern in 30 ventricular septal defect patients, 11 of whom had severe pulmonary vascular obstructive disease (Group I); 10 of whom had severe pulmonary hypertension without pulmonary vascular obstructive disease (Group II); and 9 of whom had no pulmonary hypertension and hemodynamically unimportant left-to-right shunts (Group III). In addition, 25 healthy subjects (Group IV) were studied for comparative purposes. The peak velocity of early left ventricular filling (E) was significantly lower in Group I than in all the other groups (p < 0.01). The peak velocity of late left ventricular filling (A) was significantly higher (p < 0.01) in Group I than in Group III, or than in normal individuals (Group IV) (p < 0.01). The ratio A/E was the most prominent difference between Group I patients and the other groups, with Group I having a significantly higher ratio (p < 0.01), which was 1 or greater in 9 of 11 patients. In contrast, none of the remaining ventricular septal defect patients or normal subjects had an A/E ratio of 1 or greater. Group II had increased mitral flow velocities, while Group III had normal mitral flow velocity profiles. A positive correlation between the magnitude of the left-to-right shunt and early mitral flow velocity peak (r = 0.86) and late peak (r = 0.81) was found, regardless of the degree of pulmonary hypertension. These results indicate that significant alterations of the mitral flow velocity pattern, which mimic the abnormalities associated with impaired left ventricular diastolic function (A/E ratio of 1 or greater), occur in ventricular septal defect patients who have severe pulmonary vascular obstructive disease. The transmitral velocity profiles in the ventricular septal defect patients without severe pulmonary vascular obstructive disease were similar to those of the normal patients, although the values relative to the degree of left-to-right shunting were higher in the ventricular septal defect patients. (Texas Heart Institute Journal 1989;16:270-4)